Penerapan Website Sistem Pengajuan Cuti Pegawai Pada Kantor Kecamatan Ciawi Bogor - Susilowati, Susi; Widiana, Rahmi (STIKOM Tunas Bangsa Pematangsiantar, 2019)
Limitations of the process on filing employee leave at the Ciawi Bogor sub-district office tend to be ineffective and inefficient so that in the process it makes both parties (employees and operators) have a difficulty. In addition to the leave filing files that are piled up, sometimes the operator forgets to process when there are employees who apply for leave. The research objective is to produce a web-based leave filing program so as to make it easy for users to apply for and process leave. The method of developing a software system uses the waterfall model. The results of the study in addition to displaying information about office activities or staffing on the main page, there are also facilities for filing leave, and changing the status of leave applications. Through this website employees had a view of information about the office activities and make the leave submission process online.